2021
DOI: 10.3389/fcell.2021.602887
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Metabolomics for Discovering Potential Biomarkers and Identifying Metabolic Mechanisms in Aging and Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is an aging-related neurodegenerative disease. We aimed to investigate the metabolic mechanisms of aging and AD and to identify potential biomarkers for the early screening of AD in a natural aging population. To analyze the plasma metabolites related to aging, we conducted an untargeted metabolomics analysis using ultra-high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry in a two-stage cross-sectional study. Spearman’s correlation analysis and random for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…AD-related human metabolites were collected from one recent systematic review ( Xie et al, 2021 ), which summarized 67 AD or mild cognitive impairment (MCI) patient metabolic profiling studies. Among the 67 studies, the number of AD cases ranged from 7 to 1,356, the number of MCI cases ranged from 10 to 356, and the number of healthy controls ranged from 7 to 23,882.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AD-related human metabolites were collected from one recent systematic review ( Xie et al, 2021 ), which summarized 67 AD or mild cognitive impairment (MCI) patient metabolic profiling studies. Among the 67 studies, the number of AD cases ranged from 7 to 1,356, the number of MCI cases ranged from 10 to 356, and the number of healthy controls ranged from 7 to 23,882.…”
Section: Methodsmentioning
confidence: 99%
“…However, based on the complexity of the metabolites, different tissue distributions, different detection techniques, different populations and species can systemic abnormalities in metabolomic profiles. In this study, to compare AD-specific metabolomics alterations between AD animal models and human patients, we integrate multiple metabolic profiles from AD patients ( Xie et al, 2021 ) and mouse models. Significant metabolic pathways and metabolites are identified in AD.…”
Section: Introductionmentioning
confidence: 99%
“…A high-throughput metabolomics study reported that proline metabolism plays a key role in the progression from healthy to mild cognitive impairment to AD in a natural aging population ( Xie et al, 2021 ). The disease-metabolite-pathway associations highlight the importance of proline in all three neurodegenerative diseases, including AD, PD, and ALS ( Kori et al, 2016 ).…”
Section: Proline Metabolism In Neurological and Psychiatric Disordersmentioning
confidence: 99%
“…In the case of Alzheimer's disease (AD), aging is the major risk factor with a doubling rate of incidence every five years after the age of 60 [171]. AD and aging also share several common metabolic changes in key metabolic pathways, such as the TCA cycle, the arginine biosynthesis pathway, the proline metabolic pathway and purine metabolism [172].…”
Section: Ms-based Metabolomics In Secondary Mitochondrial Diseasementioning
confidence: 99%